Experimental assessment of productivity, oil-yield and oil-profile of eight different common freshwater-blooming green algae of Kerala. (October 2016) - Santhosh Kumar, K.; Prasanthkumar, S.; Ray, J.G.
Abstract: Better strains of green algae of desirable biomass yield and oil characteristics are important to algal-based bio-industries. Biomass-yield per unit time, oil productivity per unit biomass, chemical characteristics of oil, nutritional significance and biofuel potentials of the oil of eight different common freshwater-blooming green-algae are compared. Preliminary screening for lipid richness was carried out using Sudan-black lipid staining method. Selected algae were cultured in Bold's Basal Medium under uniform laboratory condition for 30 days. Fatty acid profiling was done by GCMS and the preliminary biodiesel feasibility was confirmed by FTIR. Percentage composition of omega-3, omega-6 and omega-7 group of fatty acids was used to assess the nutritional value of the oil. Algal biomass yield of the eight species varied from 35.4% to 201.6% mg/L/Day. The biomass-yield and oil productivity of Keratococcus bicaudatus is reported for the first time, which is quite comparable to Botryococcus spp., one of the universally well known species in this regard. Another species Monoraphidium obtusum is observed to contain good quantity of omega-3 fatty acids (13.18%). The oil of the different species of algae showed 6.06–82.14% saturated fatty acids, 1.14–25.92% monounsaturated fatty acids and 0.79–41.26% polyunsaturated fatty acids. Since C14 to C18 fatty acids are considered as the feed-stock for quality based biodiesel, presence of such fatty acids in the oil of all these algae is a preliminary indication for biodiesel feasibility of the same, further confirmed by FTIR of its methyl esters. Highlights: Experimental assessment of nutritional and bio-fuel potential of eight common algae. Quite high biomass-yielding and lipid productive Keratococcus bicaudatus is found out. Oil from all the eight species are found to be rich in omega group of fatty acids. Algal oils of all the eight species are proved to have preliminary feasibility for biodiesel.